Cardiologist perceptions of family-centred rounds in cardiovascular clinical care. Issue 2 (4th September 2018) - Ludmir, Jonathan; Liu, Xinggang; Gupta, Anuj; Ramani, Gautam V; Liu, Stanley S; Zakaria, Sammy; Verceles, Avelino C; Shah, Nirav G; McCurdy, Michael T; Dammeyer, Jennifer A; Netzer, Giora
Abstract : Objective: Few data exist regarding physician attitudes and implementation of family-centred rounds (FCR) in cardiovascular care. This study aimed to assess knowledge and attitudes among cardiologists and cardiology fellows regarding barriers and benefits of FCRs. Methods: An electronic, web-based questionnaire was nationally distributed to cardiology fellows and attending cardiologists. Results: In total, 118 subjects were surveyed, comprising cardiologists (n=64, 54%) and cardiology fellows (n=54, 46%). Overall, 61% of providers reported participating in FCRs and 64% felt family participation on rounds benefits the patient. Both fellows and cardiologists agreed that family rounds eased family anxiety (fellows, 63%; cardiologists, 56%; p=0.53), improved communication between the medical team and the patient and family (fellows, 78%; cardiologists, 61%; p=0.18) and improved patient safety (fellows, 59%; cardiologists, 47%; p=0.43). Attitudes regarding enhancement of trainee education were similar (fellows, 69%; cardiologists, 55%; p=0.19). Fellows and cardiologists felt that family increased the duration of rounds (fellows, 78%; cardiologists, 80%; p=0.18) and led to less efficient rounds (fellows, 54%; cardiologists, 58%; p=0.27). Conclusion: The majority of cardiologists and fellows believed that FCRs benefited families, communication and patient safety, but led to reduced efficiency and longer duration of rounds.